Gusjigang (Bagus-Ngaji-Dagang): Mengembangkan Karakter Entrepreneurship pada Santri di Pesantren Entrepreneur Al-Mawaddah Kudus - Zunitasari, Sindy; Pramono, Didi (JOM, 2024)
Gusjigang is a philosophy brought by Sunan Kudus which is very familiar among the people around Kudus. Even his teachings are applied in various fields, one of which is in educational environments such as Islamic boarding schools. This study aims to find out about the knowledge of students in Islamic boarding schools related to the values ​​contained in the Gusjigang philosophy. In addition, to describes the social construction formed in the formation of entrepreneurial character in students. This study uses a qualitative descriptive method, with the research location at the Al-Mawaddah Entrepreneur Islamic Boarding School in Kudus. The data collection approach used includes in-depth interviews, documentation studies, and observations. The results of this study indicate that the students understand the values ​​of the Gusjigang philosophy well. This happens because the students are used to imitating, interpreting, and practicing it in everyday life, both in their behavior, religious activities, and the implementation of entrepreneurship. Then the construction built in the formation of entrepreneurial character in students continues to run repeatedly through dialectical stages, namely externalization, objectivation, and internalization.